Ocorrência de anticorpos para Neospora caninum em cães da área urbana e rural do sul do Rio Grande do Sul - Cunha Filho, Nilton Azevedo da (2007)
Neospora caninum is a protozoan parasite that causes neurological problems in dogs. It has been shown that it may act as definitive hosts of the parasite. There is a need for more information on the occurrences of N. caninum in due to the wide range of its incidence in several Brazilian states, and the lack of animals diagnosed serum positive in Rio Grande do Sul. Rural dogs from (meat and dairy producers) and urban areas from the city of Pelotas were examined. Serum samples of 339 dogs were tested for the detection of antibodies against N. caninum by indirect immunofluorescence (RIFI ≥1:50). Antibodies for N. caninum were found in 53 (15,6%) of the dogs serum samples. The occurrence in the urban area was 5,5%, among the rural dogs 14,1% (18 dogs) belonged to dairy and 28,4% (29 dogs) from cattle farms. Dogs over three years old present the higher levels of serum positively and its presence increased with age. The dogs antibody titers were 1:50 (12 dogs), 1:100 (07 dogs), 1:200 (08 dogs), 1:400 (19 dogs), 1:800 (05 dogs) and 1:1600 (02 dogs). None of the dogs examined presented clinical signs of neosporosis when the blood was collected. The study of the variables (risk factors for N. caninum) in the logistic regression between the rural and urban environment has shown that older animals are 3,75 times more likely to get infected by the N. caninum then the younger ones. Also in farms where the carcasses of dead animals are not removed there is a risk 2,67 times greater (IC 95% = 1,31 5,42) of a N. caninum infection. In the rural environment, dogs from cattle raising farms have a chance 2,24 times greater of being infected by N. caninum then dogs from dairy farms. In addition, the risk of having serum positive dogs in farms where the carcasses are not removed was more significant (OR = 6,11 IC 95% = 1,00 37,17). The data suggest that Neospora caninum is present in the southern region of Rio Grande do Sul and afflicts both rural and urban dogs. The probability of serum positive dogs in the rural area is grater, possibly by the easy access they have to infected material and the canine/bovine contact, which is characteristic of the cattle raising in the region. The main form of infection by N. caninum among the dogs studied is the horizontal (post natal), suggested by the fact that serum prevalence increase with the age.